The effect of the general anti-avoidance rule on corporate tax avoidance in China - Leung, S.; Richardson, G.; Taylor, Grantley (Elsevier, 2019)
© 2018 Elsevier Ltd This study examines the effect of the general anti-avoidance rule (GAAR), introduced on January 1, 2008, to enforce corporate tax avoidance laws in China. Based on a sample of 517 Chinese firms over the 2006–2010 period (2585 firm-years), we find a reduction in tax avoidance following the implementation of the GAAR that appears to be the result of the new and stringent tax legislation and the consolidation of Chinese tax law. We also observe that the effects of firms’ engaging a Big Four auditor and directors with tax expertise in deterring tax avoidance significantly decreased following implementation of the GAAR. To all intents and purposes, it seems that the implementation of the GAAR in China has moderated the effects of and substituted for these particular monitoring and disciplining mechanisms.